Insights Into Dendritic Cells in Cancer Immunotherapy: From Bench to Clinical Applications - Salah, Ahmed; Wang, Hao; Li, Yanqin; Ji, Meng; Ou, Wen-Bin; Qi, Nianmin; Wu, Yuehong (Frontiers in Cell and Developmental Biology, 2021)
Dendritic cells (DCs) are efficient antigen-presenting cells and potent inducers of naïve T cells. Therefore, they act as a connective ring between innate and adaptive immunity. DCs subsets are heterogeneous in their ontogeny and functions. They have proven to potentially uptake and process tumor-associated antigens (TAAs). In this regard, researchers have developed strategies such as genetically engineered or TAAs-pulsed DCs vaccines; these manipulated DCs have shown significant outcomes in clinical and pre-clinical models. Here we review DCs' classification and address how tumor microenvironment can turn DCs into an immunosuppressive phenotype. Additionally, we present the advancements in DCs as a platform for cancer immunotherapy, focusing on the technologies used for in vivo targeting of endogenous DCs, ex-vivo generated vaccines from peripheral blood monocytes, and induced pluripotent stem cells derived DCs (iPSCs-DCs) to boost anti-tumoral immunity.